Knowledge and Preventive Practices regarding Dengue Fever among Sukumbasi Basti at Lumbini Province, Nepal - Acharya, S.; Acharya, S.; Pandey, S.; Jnawali, G. (Devdaha Medical Journal, 2023)
Introduction: Dengue is a mosquito–borne tropical disease which is a major health concern across the globe. There was huge dengue outbreak worldwide in 2016. In Nepal, the first dengue case was reported in 2004 whereas Nepal had experienced a major outbreak of Dengue in several districts in 2010. The purpose of the study is to assess the knowledge and preventive practices of dengue among sukumbasi basti land people at Lumbini Province Rupandehi, Nepal.Method: A descriptive cross sectional study design was used among 179 adults (aged 18 years and above).Results: Out of total 179, 72.6% had inadequate knowledge about Dengue fever and more than half 58.1% had inadequate practice regarding prevention of dengue fever. Their knowledge had significant association with age of the respondents in years (p=0.000), educational level (p=0.001), occupation (p=0.007), religion (0.038), marital status (0.037), family history of dengue (0.023). The majorities (58.1%) of respondents did not follow the preventive practices related to Dengue fever. There was a significant association between level of practices with sex of the respondents, education level and occupation.Conclusion: It can be concluded that majorities of the respondents had inadequate knowledge regarding preventive practices of dengue and more than half of the respondents had inadequate practices regarding dengue prevention.